Exploring the trophic interactions in the coral reef ecosystem at the coastal area of Ternate Island using Ecopath model - Faizal Rumagia; Aditiyawan Ahmad; Irwan Abdul Kadir (Depik, 2025)
The Ecopath mass-balanced model was employed to elucidate the trophic structure and interaction, energy flow, and ecosystem properties of the coral reef ecosystem in the coastal area of Ternate Island. The model comprised 30 functional ecological groups, of which 29 were living groups and one was a group of detritus. The trophic structure of the model exhibited a range of values, from 1.0 for primary producers and detritus to 3.81 for the top predator. The resulting trophic aggregation comprises six effective trophic groups, with the largest energy flow originating from zooplankton and benthic organisms in trophic level II. The transfer efficiency is predominantly derived from detritus organisms, in comparison to that derived from phytoplankton as the primary producer. The ratio of total primary production per total respiration indicated that the coral reef ecosystem was at a developmental stage. The coral reef ecosystem exhibited a low ecological efficiency for the fishery gross efficiency. Mixed trophic impact analysis indicated that predators exerted a negative impact on their prey, whereas planktonic organisms exerted a positive impact on the majority of fish functional groups. The comparison of the model with other studies provided information that could inform the development of appropriate fisheries management guidelines for this area based on ecosystem properties.Keywords:Coral reef ecosystemEcopathEcosystem propertiesTernate IslandTrophic interaction